Penerapan Bimbingan Karir Untuk Meningkatkan Kesiapan Kerja Siswa SMKN 2 Painan - Muharleni; Yarmis Syukur; Taufik (Suria Academic Press, 2025)
Career guidance is a crucial component in vocational education to prepare students for entering a competitive job market. This study aims to analyze the implementation of career guidance services at SMKN 2 Painan and their impact on students’ job readiness. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation. The findings show that career guidance at SMKN 2 Painan is implemented progressively from grade X to XII through various strategies such as interest- aptitude assessments, career seminars, industrial visits, job skills training, and individual counseling. These services significantly enhance students’ career understanding, self-efficacy, and practical competencies. However, implementation still faces several challenges, including low student motivation, limited counseling staff, and underdeveloped partnerships with industry. The study recommends strengthening career services through institutional integration, capacity building for counselors, and sustainable inter-institutional collaboration.